Leptin concentrations in African blacks with metabolic syndrome and Type 2 diabetes mellitus (2011)
Background: Mortality rate from metabolic/cardiometabolic syndromes (MS/CMS) and type 2 diabetes mellitus (DM2) are highly prevalent in African blacks known with higher mortality from cardiovascular diseases than caucasians. Leptin, a satiety-regulating hormone increases in obesity and is associated with cardiovascular risk and prediction of MS. This study is designed to evaluate leptin in Nigerians with MS and DM2 to assist in the early diagnosis and prevention of metabolic diseases. Methods: 136 participants (45 with MS, 47 with DM2 and 44 apparently healthy individuals (controls)) aged 18-80 years were included in a cohort study at the University College Hospital, Ibadan. Measures of adiposity-%body fat, body mass index (BMI), waist and hip circumferences (WC and HC respectively), waist to hip ratio (WHR), and blood pressure were obtained by standard methods. 10 ml of blood were obtained from each participant after an overnight fast (10-14 h) and analysed for leptin, total cholesterol (TC), triglycerides (TG), high density lipoprotein (HDL), and glucose by standard methods while low density lipoprotein (LDL) was calculated. Data obtained were analysed statistically with SPSS software version 16.0. Results: Weight, BMI, WC, HC, WHR, %body fat, blood pressure, TG, LDL-C, and glucose were significantly higher while HDL-C was significantly lower in individuals with MS and DM2 compared with controls (p<0.039). Leptin levels were significantly higher in MS group and not in DM2 group when compared with controls (p=0.000). Leptin did not correlate with any of the biochemical indices (p>0.05) tested but correlated significantly with different measures of adiposity in all groups. Leptin correlated negatively but significantly with blood pressure in MS group only. Conclusion: Increases in leptin levels in both MS and DM2 groups might reflect adiposity. Observed high leptin levels in MS group might be a compensatory mechanism for maintenance of weight/fat loss and blood pressure. Its routine analysis may assist in assessing adiposity associated with MS and DM2 for probable prevention of metabolic diseases.